From Hollywood to the Ummah: The Role of Islamic Broadcasting in Reshaping Perceptions of Islam in Response to Film Stereotypes - Alamyar, Iqbal Hussain; Mustain; Ziaulrahman Mushkalamza (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2024)
The study investigates the problem of stereotypes about Islam propagated by Hollywood films and the role of Islamic broadcasting in reshaping these perceptions. The objective of this research is to understand the impact of Hollywood’s portrayal of Islam on public perceptions and to explore how Islamic broadcasting counters these stereotypes and fosters a more accurate understanding of Islam. The research employs a qualitative approach, using methods such as in-depth interviews and document analysis. The data collected is analyzed using thematic analysis, ensuring the validity and reliability of the findings. The findings reveal a significant influence of Hollywood’s portrayal on public perceptions of Islam. However, Islamic broadcasting has emerged as an effective medium for countering these stereotypes and promoting a more balanced view of Islam. The study concludes that Islamic broadcasting plays a crucial role in reshaping perceptions of Islam, countering the stereotypes perpetuated by Hollywood. The implications of these findings suggest a need for further research into the power of broadcasting in shaping religious perceptions.